Mesorectal fat area and mesorectal area affect the surgical difficulty of robotic‐assisted mesorectal excision and intersphincteric resection respectively in different ways. (6th March 2020) - Huang, S.; Chen, M.; Deng, Y.; Wang, X.; Lu, X.; Jiang, W.; Huang, Y.; Chi, P.
Abstract: Aim: Many studies have demonstrated predictors of the difficulty of laparoscopic anterior resection for rectal cancer. Few studies focus on the influence of pelvic dimensions on robotic‐assisted mesorectal excision (ME) and intersphincteric resection (ISR). This study aimed to evaluate the influences of the mesorectal fat area (MFA) and mesorectal area on the difficulty of robotic sphincter‐saving surgery. Methods: We included 156 patients with middle and low rectal cancer who underwent robotic sphincter‐saving surgery. Clinical and anatomical factors, including the pelvic dimensions, were collected. Linear regression was performed for variables associated with surgical duration. We also performed subgroup analyses for robotic‐assisted ME and ISR. Logistic regression was used to find variables associated with transanal dissection. Results: For patients with middle or low rectal cancer, the sacral length and tumour distance from the anal verge were independently associated with surgical duration. The pT stage, sacral length and the MFA were independent predictors for the surgical duration of robotic‐assisted ME. By contrast, a small mesorectal area was independently related to a longer duration of robotic‐assisted ISR. The pelvic outlet length was independently associated with the use of transanal dissection for ISR. Conclusion: It is suggested that a large MFA could affect the difficulty of ME in robotic‐assisted ME, while a small mesorectal area could increase the surgical difficulty of robotic‐assisted ISR for low rectal cancer. Besides, the pelvic outlet length was associated with the use of transanal dissection. Further studies are needed to validate the results and draw more scientific conclusions.